Management-induced micro-habitats in crop fields alter the trait composition of arable plant communities - Elsa Lagerquist; Göran Bergkvist; Alexander Menegat (Basic and Applied Ecology, 2025)
Modern cropping systems typically involve extensive soil disturbance and high fertiliser use. Plants other than the crop are controlled to avoid potential crop yield losses. However, crop fields are not homogeneous ecosystems. Rather, they comprise several micro-habitats differing in disturbance intensity, inter-specific competition and resource availability. Understanding how weed and crop management affects the trait composition of arable plants could help finding management practices that favour less competitive species or species providing valuable ecosystem services. This study examined the traits within the arable plant community and their association with disturbance and competition levels. The relationship between micro-habitats and plant species traits was investigated using RLQ analysis, in which micro-habitats and traits were linked using species count data. The environmental variables forming micro-habitats were: biomass of main crop and intercropped service crop, frequency of mechanical disturbance and within-crop sampling location. Intermediate to high competition and intermediate disturbance reduced the presence of competitive arable plant species compared with low competition and highest and lowest disturbance, while favouring a diverse group of ruderal species. High service crop biomass in the main crop row, compared with low, reduced the presence of arable plant species that were associated both with ruderal and competitive traits (competitive-ruderals), while favouring the diverse group of ruderal species. The analysis showed distinctions in traits associated with different micro-habitats, but to better guide interpretations regarding species’ harmfulness to crops, species characteristics based on combinations of traits have to be defined at a finer scale, especially for ruderal species.